Method for forming transparent conductive film and powder target
By using a powder target of mixed zinc oxide, GZO, or AZO powders, the method addresses the challenge of forming transparent conductive films on heat-sensitive resin substrates, achieving low electrical resistivity and uniformity in film properties at room temperature.
Patent Information
- Application Number
- JP2023149883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Conventional methods for forming transparent conductive films on glass substrates are not suitable for polymer or resin substrates due to heat sensitivity, and sputtering methods often result in variations in film properties, especially when deposited at room temperature.
A method for forming a transparent conductive film on a transparent resin substrate using a powder target made by mixing zinc oxide powder with gallium-added zinc oxide (GZO) or aluminum-added zinc oxide (AZO) powder, and adjusting the sputtering conditions to achieve an electrical resistivity of 1x10^-3 Ωcm or less, even at room temperature.
This method allows for the formation of transparent conductive films with low electrical resistivity on resin substrates without the need for heat treatment, reducing variations in film properties and enabling the production of flexible transparent conductive sheets.
Smart Images

Figure 2025042765000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a technique for forming a transparent conductive film on a transparent resin substrate, which can also be applied to a flexible transparent conductive sheet. [Background technology]
[0002] Conventionally, indium oxide-based materials, such as ITO, have been known from the viewpoint of electrical resistivity as materials for forming transparent conductive films on glass substrates. Such transparent conductive films are used in a variety of applications, including touch panels, solar cells, and transparent heaters. On the other hand, the material indium is expensive, and there are concerns about environmental pollution during refining, so alternative materials have been considered for some time. One of these is zinc oxide, which is inexpensive and said to have no impact on health, and gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO), which are based on this, are known.
[0003] There are also various methods for depositing films, among which the sputtering method, which involves placing a substrate and a target material opposite each other and bombarding the target material with gas such as Ar under vacuum to deposit the material on the substrate, has the advantage of being able to deposit films on large substrates at high speeds, making it a method that is easily adapted to industrial mass production.
[0004] ITO is approximately 1×10 -4 Ωcm~2×10 -4 is the electrical resistivity in Ωcm. When using GZO or AZO, the top data for the electrical resistivity of the sputtering film is 2×10 -4 Since it is Ωcm, it is approximately (1~3)×10 -3 One guideline is that the film can be formed so that the resistivity is about Ωcm or less. Also, for transparency, a guideline is that the visible light transmittance is 80% or more.
[0005] However, the conventional techniques have the following problems. The sputtering method is prone to variation in characteristics, and has the problem that, for example, when a film is formed using a circular target on opposing substrates, erosion occurs at a certain distance from the center, resulting in high electrical resistivity in the corresponding area (opposing position). In addition, when the chamber is heated to 200 to 300°C and the conditions are adjusted, the glass substrate has an electrical resistivity of 3×10 -4 Ωcm~3×10 -3 It is possible to form GZO and AZO films with good resistivity of Ωcm, but when formed at room temperature without heating, the electrical resistivity becomes orders of magnitude higher. However, even when formed at room temperature, it is possible to reduce the electrical resistivity by performing a heat treatment (annealing) after film formation. That is, in order to form a high-quality film, it is necessary to perform heating during film formation or to heat the film after it has been formed. In either case, there is a problem that it is not possible to form a film on a polymer substrate or a resin substrate, which are sensitive to heat. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2020-033594 [Non-patent literature]
[0007] [Non-Patent Document 1] Y.Yamada, et.al, 'Positional variation and annealing effect in magnetron sputtered Ga-doped ZnO films', Thin Solid Films 609(2016), 25-29 [Non-Patent Document 2] Yumika Yamada et al., "In-plane distribution of electrical properties in Zn-doped GZO films," 2019 Joint Academic Conference of the Chugoku-Shikoku Branch of Applied Physics and Physics Societies Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in view of the above, and has an object to provide a technique for forming a transparent conductive film on a transparent resin substrate. [Means for solving the problem]
[0009] The method for forming a transparent conductive film described in claim 1 is characterized in that a powder target in which gallium-doped zinc oxide (GZO) powder or aluminum-doped zinc oxide (AZO) powder is mixed with zinc powder is used to form a transparent conductive film on a transparent resin substrate by a sputtering method at room temperature. By adjusting the conditions, such as by separating the substrate and the target, the electrical resistivity can be increased to 1×10 -3 It is possible to form a transparent conductive film with a resistance of about Ωcm or less. In the present invention, the gallium-doped zinc oxide (GZO) powder or the aluminum-doped zinc oxide (AZO) powder also includes a mixed powder of GZO powder and AZO powder.
[0010] A method for forming a transparent conductive film according to a second aspect of the present invention is characterized in that a powder target in which magnesium powder is further mixed in addition to the method for forming a transparent conductive film according to the first aspect of the present invention. It is possible to further reduce the electrical resistivity.
[0011] The method for forming a transparent conductive film according to a third aspect of the present invention is characterized in that, in the method for forming a transparent conductive film according to the first or second aspect, a transparent resin substrate that has been heat-treated at a predetermined temperature is used. In comparison with the case where no prior heat treatment is performed, the electrical resistivity can be reduced, and the variation can also be reduced.
[0012] The method for forming a transparent conductive film described in claim 4 is characterized in that, in the method for forming a transparent conductive film described in claim 1, a flexible substrate made of polyethylene terephthalate, polyethylene naphthalate, polyimide, or thermoplastic aromatic polyamide is used as the transparent resin substrate. It is also possible to form a flexible transparent conductive sheet as a thin substrate.
[0013] The powder target described in claim 5 is a target for forming a transparent conductive film on a resin substrate by a sputtering method, and is characterized in that zinc powder is mixed with gallium-doped zinc oxide (GZO) powder or aluminum-doped zinc oxide (AZO) powder. By adjusting the conditions, the electrical resistivity can be increased to 1×10 -3 It is possible to form a transparent conductive film with a resistance of about Ωcm or less.
[0014] The powder target according to a sixth aspect of the present invention is characterized in that, in the powder target according to the fifth aspect, magnesium powder is further mixed therein. It is possible to further reduce the electrical resistivity.
[0015] The amount of gallium in GZO can be optimized from the viewpoint of electrical resistivity, etc., depending on the degree of vacuum in sputtering, applied voltage, amount of power, distance between the target and the substrate, etc., but it can be set to about 1 at% to 6 at% of the number of metal atoms contained in the entire GZO powder. With 1 at% addition, the electrical resistivity of the conductive film is about 1 x 10 -1 Ωcm or less, and 2×10 -3 If it is less than 1 at%, the effect of addition is small, and if it exceeds 6 at%, the electrical resistivity gradually increases and other physical properties deviate from the required specifications. The amount of aluminum in AZO is similar. Zinc powder refers to pure zinc powder, and its amount can be about 5 at% to 20 at% based on the number of metal atoms contained in the entire powder. In the case of a target consisting of only GZO powder or AZO powder (and even a mixture of these powders), the electrical resistivity increases by an order of magnitude as the distance between the target and the substrate increases during film formation at room temperature. However, by adding zinc powder, it is surprisingly possible to achieve film formation at room temperature with such an increase suppressed. Addition of 5 at% or more realizes stable suppression of the increase in electrical resistivity with little variation due to film formation conditions. Addition of 15 at% or more increases the effect of adhesion to the inner wall of the chamber. The amount of addition is preferably 5 at% to 15 at%, with a center of about 10 at%. The magnesium powder further added as necessary is pure magnesium powder, and the amount added is generally 2.5 wt% or less, preferably 0.5 wt% or less, based on the total amount of powder. If it is 0.5 wt% or less, there is virtually no effect on transparency, but if it is 2.5 wt% or more, transparency will decrease in some places. The thickness of the transparent resin substrate and the transparent conductive film are not particularly limited, but for example, a flexible transparent conductive sheet can be formed with a substrate of 250 μm and a film thickness of 500 nm. The preliminary heat treatment of the substrate may be, for example, set to a temperature in the range of 80°C to 200°C and maintained for 30 minutes. Preferably, the heat treatment is set to a temperature in the range of 80°C to 150°C and maintained for 30 minutes. The melting points of polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are 260°C and 265°C, respectively, while polyimide (PI) has no melting point and a thermal decomposition temperature of 500°C or higher. In cases where the heat resistance range is wide, including polyamide, a material having heat resistance according to the appropriate specifications should be used. Effect of the Invention
[0016] According to the present invention, a transparent resin substrate is coated with a thin film having an electrical resistivity of 1×10 -3 It is possible to form a transparent conductive film with a resistance of about Ωcm or less. [Brief description of the drawings]
[0017] [Figure 1] This is a graph showing the relationship between the distance r from the center and the electrical resistivity ρ of a conductive film formed at room temperature by sputtering using GZO powder as a target, by changing the target-substrate distance dts. [Diagram 2] 13 is a graph showing the relationship between r and ρ when a mixed powder target in which Zn powder is added to GZO powder is used. [Diagram 3] 1 is a graph showing the relationship between dts and ρ in film formation at room temperature when a mixed powder target of GZO powder and Zn powder is used. [Figure 4] 1 is a graph showing the relationship between dts and ρ for a conductive film formed on a transparent resin film substrate by room temperature sputtering using a mixed powder target. [Diagram 5] 1 is a photograph showing the surface properties of a conductive film formed on a transparent resin film substrate by sputtering at room temperature using a mixed powder target. [Figure 6] 1 is a graph showing p of a conductive film formed on a resin substrate that has been heat-treated in advance by room temperature sputtering using a mixed powder target. [Figure 7] 1 is a graph showing the surface properties of a conductive film formed on a resin substrate that has been heat-treated in advance by room temperature sputtering using a mixed powder target. [Figure 8] 13 is a graph showing the relationship between the amount of Mg powder added to the mixed powder and ρ. [Figure 9] This is a photograph showing the surface properties of a film formed by room temperature sputtering instead of a resin substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. <Test 1 (preliminary test): Electrical resistivity when film is formed at room temperature> First, film formation was performed at room temperature (non-heated film formation), and the relationship between the distance r from the target center of the conductive film formed and the electrical resistivity ρ was investigated by changing the distance dts between the target and the substrate. Although the inside of the chamber is not heated, it is expected that radiant heat will be generated and cause damage such as deformation of the resin substrate. Therefore, in order to investigate the properties of the conductive film itself that is formed, it was decided to form the film on a glass (SiO2) substrate.
[0019] The magnetron sputtering equipment used for sputtering (Nichiden Anelva SPF210H or Canon Anelva Engineering E-400S) was Ar gas, with a sputtering output of 200 W and an AC frequency of 13.56 MHz. During sputtering, the target material was placed horizontally and a substrate was placed horizontally above it. The equipment and arrangement described here were the same for the following tests.
[0020] First, the target material was composed only of GZO powder, and the electrical resistivity ρ of the film formed was examined. The GZO powder was produced in-house using Ga2O3 and ZnO, mixed so that Zn was 5 at% (both manufactured by Kojundo Chemical Laboratory. Ga2O3: product number GAO04PB, ZnO: product number ZNO07PB). The shape of the target material was a flattened cylinder (diameter 10 cm x thickness 5 mm. The target shape was the same in the following tests). No special treatment such as sintering was performed on the raw powder.
[0021] The results are shown in Figure 1. As is clear from the figure, in the erosion region at r = 20 mm to 30 mm from the center of the substrate, the electrical resistivity ρ of the conductive film formed opposite to it rises in a mountain-like shape, and it can be confirmed that it becomes higher as dts increases (conductivity becomes worse). Even when dts = 50 mm, where ρ is at its smallest, in the erosion region, ρ is ~10 -2 The resistivity increases to nearly Ωcm and the required specifications are no longer met. When the magnetron sputtering apparatus of the present application is used, the film thickness varies depending on the distance of dts, but when dts=50 mm, the film thickness is approximately 500 nm to 600 nm, and when dts=100 mm, the film thickness is approximately 200 nm.
[0022] <Test 2: Effect of mixing Zn powder 1> Next, the target was a mixed powder of GZO powder and Zn powder. The Zn powder content in the mixed powder was 10 at% (manufactured by Kojundo Chemical Laboratory Co., Ltd. Zn: product number ZNE06PB). Unless otherwise specified, the amount of Zn powder added was the same in the following tests. Figure 2 shows the relationship between r and ρ when dts = 50 mm. For comparison, the results for GZO powder only are also shown. Note that although the conditions were the same as in Test 1, because there is a large variability in sputtering, evaluation tests for GZO powder and GZO powder + Zn powder were conducted consecutively in addition to Test 1. As is clear from the figure, by simply adding Zn powder, no increase in ρ was observed in the erosion region (almost no difference in ρ due to r was observed), and, surprisingly, a reduction in ρ of one to two orders of magnitude was observed. -4 This enables deposition of films with low resistivity on the order of Ωcm.
[0023] <Test 3: Effect of mixing Zn powder 2> Test 2 confirmed that by using a powder target mixed with Zn powder, ρ becomes almost constant regardless of location. Therefore, we decided to use the ρ of the conductive film formed at the substrate position facing the center of the target as a representative value and investigate the relationship between ρ and dts. The results are shown in Figure 3. For comparison, we also show the results of using a target containing only GZO powder without the addition of Zn powder. As is clear from the figure, when Zn powder is added, ρ does not increase by even an order of magnitude even when dts is doubled from 50 mm to 100 mm (ρ increases gradually and linearly). On the other hand, when Zn is not added, ρ increases nonlinearly and steeply as dts increases, and when dts=50 cm, ρ is 10 -3Ωcm, and in the case of 70cm, ρ~10 -1 The conductivity has deteriorated to the Ωcm range.
[0024] Tests 2 and 3 show that the target material in which Zn powder is mixed with GZO powder not only reduces ρ, but also does not result in an increase in ρ in the erosion region (i.e., ρ is roughly constant everywhere, regardless of location), and that ρ only increases gradually even if dts increases.
[0025] <Test 4: AZO powder + Zn powder> Next, we investigated the case where AZO powder was used as the target instead of GZO powder, and also the case where a mixed powder of AZO powder and Zn powder was used as the target. The AZO powder was produced in-house using Al2O3 and ZnO, with the Al content being 5 at% (manufactured by Kojundo Chemical Laboratory Co., Ltd., product number ALE16PB). The Zn powder content in the mixed powder of AZO powder and Zn powder was 10 at%. Although it depends on the pressure inside the device, when dts = 50 mm, the ρ of the conductive film formed on the substrate facing the center of the target is 1 × 10 -3 Ωcm, and for mixed powders it is (4~5)×10 -4 It was Ωcm. In addition, when a mixture of AZO powder and Zn powder was used, the same results as those shown in Figures 2 and 3 were obtained. Although not shown in the figures, the electrical resistivity of the area directly above the target center and the area corresponding to erosion was essentially the same, and both were 1×10 -3 (In the case of a target containing only AZO powder, the electrical resistivity of the film formed directly above the center was ρ = 4 × 10 -2 Ωcm, ρ=1×10 in the erosion region -1 Ωcm).
[0026] As described above, in the past, when non-heated film formation was performed by sputtering using GZO powder or AZO powder as the target material, it was known that as dts increased, ρ would rise overall in a bottom-up manner, and in the erosion region it would become even more mountain-like, and a resistivity increase of a different order of magnitude would be the norm, and a practical transparent conductive film would not be formed. However, when a powder target material in which Zn powder was added to GZO powder or AZO powder was used, it was found that no increase in ρ of an order of magnitude was observed (and no matter where) even when the spacing was increased.
[0027] Therefore, the inventors of the present application have invented the following as a result of extensive research. In non-heating film formation by sputtering, if dts is small, then ρ is small, but the substrate temperature rises due to radiant heat, etc., and substrates that are not highly heat-resistant, such as resin substrates, cannot be used, but in the case of the target material of the present invention, GZO powder or a mixed powder of AZO powder and Zn powder, even if dts is increased to avoid the influence of heat, film formation can be performed while suppressing the increase in ρ. In other words, it is possible to form a transparent conductive film having a practical resistivity on a resin substrate, particularly a transparent resin sheet.
[0028] <Test 4: Film formation on resin substrate> Therefore, the target material was a mixture of GZO powder and Zn powder, and the resin substrate was a PET film (PET film: Lumirror T60 manufactured by Toray Industries, Inc., thickness 250 mm) and the dts was changed to form a film. For comparison, a film was also formed using only GZO powder.
[0029] The results are shown in Figure 4. An optical photograph of the transparent thin film surface is shown in Figure 5. When dts was 60 mm or less, the PET substrate was altered by heat and ρ could not be measured. When dts was 65 mm or more, cracks appeared in the substrate, but ρ as a conductive film increased by 10 -2 It rises to about Ωcm, but then drops to 10 -3In any case, ρ is at least one order of magnitude smaller than when only GZO powder is used. Also, the larger the dts, the coarser the cracks become.
[0030] <Test 5: Film formation on heat-treated resin substrate> Based on Test 4, we thought that a substrate that had been subjected to a thermal history in advance might have better resistance than a substrate that was suddenly exposed to radiant heat, so we next considered deposition using a resin substrate that had been heat-treated in advance. Specifically, the same PET film substrate as in Test 4 was subjected to deposition without heat treatment at 80°C for 30 min, 100°C for 30 min, 150°C for 30 min, and 200°C for 30 min with dts=70 mm. The results are shown in Figure 6. An optical photograph of the transparent thin film surface is shown in Figure 7. As is clear from the figure, heat treatment, especially pre-heat treatment at 100°C to 150°C, reduces ρ by nearly one order of magnitude compared to no heating, by approximately 10 -3 Although cracks are visible, a certain degree of transparency is maintained.
[0031] <Test 6: Effect of Mg addition> Next, a film was formed using a target in which Mg powder was added to a mixed powder of GZO powder and Zn powder (Ga was 5 at% of the total number of metal atoms in the mixed powder, and Zn from the Zn powder was 10 at%). The amount of Zn powder added was 0.5 wt% and 2.5 wt% to the mixed powder of GZO powder + Zn powder (Zn: manufactured by Kojundo Chemical Laboratory Co., Ltd., product number ZNE06PB). The results are shown in Figure 8. Adding only 0.5 wt% of Mg reduces the resistivity by half to 5×10 -4 Ωcm. With an addition of 2.5wt%, the resistivity increased in the erosion-resistant region, but when the deposition substrate was observed, blackening was observed, and it was confirmed that transparency was not sufficiently secured. With an addition of 0.5wt%, the transmittance exceeded the index of 80%, and it was confirmed that there were no problems even when visually inspected. Therefore, it can be said that it is preferable to add a small amount of Mg, from 0.5wt% to 1.0wt%, depending on the required specifications.
[0032] As explained above, according to the present invention, by adopting a powder target in which Zn powder and, if necessary, Mg powder are added to GZO powder or AZO powder, a sputtering method suitable for industrial mass production can be used, and even under room temperature film formation conditions, it is possible to achieve a greater reduction in ρ, suppression of the increase in ρ in the erosion region (realization of uniform electrical resistivity regardless of position), and suppression of the significant increase in ρ when dts (spacing) becomes large (achievement of a gradual increase in ρ) than when GZO powder or AZO powder is used alone. By preparing the necessary conditions, it is possible to achieve a ρ of 2.9×10 -4 Film deposition of Ωcm can be achieved. In addition, according to the present invention, by separating the substrate and the target by a predetermined distance or more, it is possible to perform 10 -3 Transparent conductive films on the order of Ωcm can also be formed. [Industrial Applicability]
[0033] As a transparent substrate, instead of polyethylene terephthalate (PET), which has particularly excellent transparency, polyethylene naphthalate (PEN), polyimide (PI), which has particularly excellent heat resistance, or heat-resistant polyamide can also be used. Figure 8 shows surface photographs of examples of film formation on PET, PEN (Teonex Q51, manufactured by Toyobo Co., Ltd., 250 μm thick), and PI (Upilex 125S, manufactured by UBE Co., Ltd., 125 μm thick) by room temperature sputtering using a target of a mixed powder of AZO powder + Zn powder under the same conditions as before. Regarding the electrical resistivity, when the transparent substrate was a PEN sheet (250 μm) and a heat-resistant polyamide (manufactured by Unitika Ltd., product name Uniamide 250 μm) and the film was formed at dts = 80 mm, both had a ρ = 1.5 × 10 -3 It was Ωcm.
Claims
1. A powder target made of gallium-doped zinc oxide powder or aluminum-doped zinc oxide powder mixed with zinc powder was used. A method for forming a transparent conductive film, comprising forming a transparent conductive film on a transparent resin substrate at room temperature by a sputtering method.
2. 2. The method for forming a transparent conductive film according to claim 1, further comprising the step of using a powder target in which magnesium powder is further mixed.
3. 3. The method for forming a transparent conductive film according to claim 1, wherein a transparent resin substrate which has been heat-treated at a predetermined temperature is used.
4. 3. The method for forming a transparent conductive film according to claim 1, wherein the transparent resin substrate is a flexible substrate made of polyethylene terephthalate, polyethylene naphthalate, polyimide, or thermoplastic aromatic polyamide.
5. A target for forming a transparent conductive film on a resin substrate by a sputtering method, A powder target comprising zinc powder mixed with gallium-doped zinc oxide powder or aluminum-doped zinc oxide powder.
6. 6. The powder target according to claim 5, further comprising magnesium powder mixed therein.
Citation Information
Patent Citations
Magnetron sputtering apparatus and method of manufacturing metal oxide film
JP2020033594A
Cited By
Transparent conductive heating material and preparation method thereof
CN121518997A